Patorani fisherman's house at the Galesong Coast - Idrus, Raeny Tenriola; Hamsah, Baharuddin; Mulyadi, Rosady; Bangsawan, Nurul Jamala (2024)
This research is based on the life of Patorani fishermen on the coast when they first settled, the process of working as Patorani fishermen, and the factors that influence it. Case study on the coast of Palalakang Village, Galesong District, Takalar Regency. This type of research is qualitative descriptive research. The data collection were made from observation, interviews and documentation. Reviewing literature, including theory, expert opinions and research results, is the method carried out as a data source. Data collection including literature review, data presentation, data reduction and conclusion drawing are the data analysis techniques used. The conclusion that can be drawn from this research is that the houses of fishermen in Palalakang Village who are Patorani fishermen began the process of working as Patorani fishermen. The formation process is influenced by factors: initial history such as the residence where residence is close to the place of work, natural resources, social, cultural, economic, knowledge, philosophy of life and local wisdom.